Numerical Method for the Deterministic Kardar-Parisi-Zhang Equation in Unbounded Domains (Communications in Computational Physics, 2006)
We propose an artificial boundary method for solving the deterministic\rKardar-Parisi-Zhang equation in one-, two- and three- dimensional unbounded domains.\rThe exact artificial boundary conditions are obtained on the artificial boundaries. Then\rthe original problems are reduced to equivalent problems in bounded domains. A finite difference method is applied to solve the reduced problems, and some numerical\rexamples are provided to show the effectiveness of the method.
Keywords: Quasilinear parabolic equation; artificial boundary condition; viscous HamiltonJacobi equation; unbounded domain.